A modernidade de Max Weber: abordagens sobre o processo de racionalização e seus reflexos no direito - Arruda, Julia Peixoto de Azevedo (2012)
This dissertation lays out the main elements that make up the rationalization process discussed by Max Weber throughout his work, which results in the singularity of modern Western civilization and disenchantment of the world , as well as the effects of this process in the meaning of sciences, especially legal science, in modernity. To that effect, special attention is given to Weber s reflections on this respect in his classic essays Intermediate reflection and Science as a vocation. For proper comprehension of the rationale developed by Weber in said essays, this dissertation also examines, in general terms, Weber s sociology of religion and scientific methodology. Based on these elements, this dissertation proposes an examination of Weberian thought on law within a larger context of his sociology of modernity in order to identify the contribution of law to the rationalization process and the effects suffered by it as a consequence of the same process